Kritik Sosial Puisi “Sia-Sia” Karya Chairil Anwar Dengan Pendekatan Feminisme - Hartati, Difa; Amelia, Regita; Nanda, Sabrina Pramesuary Dwi; Sulistyani, Shiwi; Harahap, Syarafina; Nazra, Yulisin; Sipayung, Atika Wasilah (Asosiasi Ide Bahasa Kepri, 2025)
This article analyzes the poem “Sia-Sia” by Chairil Anwar through a feminist literary approach to explore the representation of women and the inequality of gender relations depicted in the poem. The research employs a descriptive qualitative method with content analysis techniques focused on close reading of the text. The primary data source is the poem “Sia-Sia”, which is interpreted using feminist theories, particularly existentialist feminism that highlights how women are marginalized within patriarchal systems. The analysis reveals that the female figure is portrayed as someone who sacrifices and gives everything, only to be rejected without clear reason, while the male figure holds the dominant role in deciding the course of the relationship. This dynamic reflects emotional dominance and unequal power relations, where the woman remains in a subordinate and powerless position. This study contributes to Indonesian literary criticism by offering a new interpretative perspective on Chairil Anwar’s work and enriching feminist literary discourse by demonstrating how literature can reflect and critique social structures that marginalize women.